Structural integrity assessment of the welded joints of the constitution of 1812 bridge (Cádiz, Spain). (August 2018) - Díaz García, M.A.; Cicero, S.; Ramos Gutiérrez, O.R.
Abstract: As required by the current Spanish regulations, an inspection and maintenance plan has been completed for the Constitution of 1812 Bridge over the Bay of Cádiz (Spain), which defines the work to be performed on the different elements of the bridge during its service life. The part of the plan related to the inspection of the steel structure has a section dedicated to the inspection of the defects that may be present in the welded joints of the steel deck, providing critical defect sizes above which the safety of the structure would be compromised. With this purpose, in the most stressed points of the deck, the structural details that are most susceptible to fatigue and fracture phenomena have been identified. Moreover, fatigue tests of these details have been performed to complete a structural integrity assessment that also comprises the determination of the material fracture toughness and the definition of the corresponding critical crack sizes. The tests were carried out on specimens obtained with the same steel grades as those used in the bridge and with the same welding procedures as those practiced in the structure. The results show that the fatigue test results are above the SN curves provided by the Eurocode 3, and also that numerous critical crack sizes would not be detected by the usual inspection techniques used in bridges (visual inspection), so that further research into how to manage this issue is recommended. Highlights: An inspection and maintenance plan has been completed for a singular bridge. Structural details most susceptible to fatigue and fracture were identified. Fatigue tests were performed to complete a structural integrity assessment. It also comprises the definition of corresponding critical crack sizes.